2021
DOI: 10.3390/beverages7030067
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Nanoencapsulated Essential Oils of Tasmannia lanceolata, Backhousia citriodora and Syzygium anisatum against Weak-Acid Resistant Zygosaccharomyces bailii in Clear Apple Juice

Abstract: The anti-yeast activity of oil-in-water encapsulated nanoemulsion containing individual or a combination of the three essential oils of Tasmanian pepper leaf (Tasmannia lanceolata), lemon myrtle (Backhousia citriodora), and anise myrtle (Syzygium anisatum) against weak-acid resistant Zygosaccharomyces bailii in clear apple juice was investigated. The effectiveness of the shelf-life extension of Z. bailii-spiked (1 × 103 CFU/mL) clear apple juice was evaluated and compared between natural (essential oils) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…deceptionensis CM2 of chicken fillets during storage at 4 °C for up to 15 days [ 22 ]. Similarly, Alderees et al [ 35 ] investigated the antifungal activities of nanoencapsulated essential oils extracted from Tasmanian pepper leaves, lemon myrtle, and anise myrtle. The results showed that the prepared EOs nanoemulsion exhibited dose- and time-dependent antimicrobial activity against Zygosaccharomyces bailii in clear apple juice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…deceptionensis CM2 of chicken fillets during storage at 4 °C for up to 15 days [ 22 ]. Similarly, Alderees et al [ 35 ] investigated the antifungal activities of nanoencapsulated essential oils extracted from Tasmanian pepper leaves, lemon myrtle, and anise myrtle. The results showed that the prepared EOs nanoemulsion exhibited dose- and time-dependent antimicrobial activity against Zygosaccharomyces bailii in clear apple juice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alderees et al [ 35 ] investigated the antifungal activities of nanoencapsulated essential oils extracted from Tasmanian pepper leaves, lemon myrtle, and anise myrtle. The results showed that the prepared EOs nanoemulsion exhibited dose- and time-dependent antimicrobial activity against Zygosaccharomyces bailii in clear apple juice [ 35 ]. The SEM results revealed that CON-treated cells showed a rough and deformed surface morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the paper by Alderees et al [10] outlines the antimicrobial activity of an oilin-water-encapsulated nanoemulsion containing either an individual oil or a combination of three essential oils of Tasmanian pepper leaf (Tasmania lanceolate), lemon myrtle (Backhousia citriodora), and anise myrtle (Syzygium anisatum) against weak-acid-resistant Zygosaccharomyces bailii in clear apple juice. The results of this study clearly indicated that essential oils of lemon myrtle and Tasmanian pepper leaf as individual oils, as well as the combination of anise myrtle and Tasmanian pepper leaf, were effective for controlling the growth of the yeast in clear apple juice within the studied storage period (28 days) and temperature (25 • C), highlighting the great potential of native Australian herbs in controlling one of the most resistant yeasts to the action of weak-acid preservatives in clear apple juice.…”
mentioning
confidence: 99%